Effect of single session counselling on partner referral for sexually transmitted infections management in Bangladesh. Issue 1 (23rd July 2010) - Alam, Nazmul; Streatfield, Peter Kim; Shahidullah, M; Mitra, Dipak; Vermund, Sten H; Kristensen, Sibylle
Abstract : Objectives: This study evaluated the role of single session counselling on partner referral among index cases diagnosed as having sexually transmitted infections (STIs) in Bangladesh. Methods: A quasirandomised trial was conducted in 1339 index cases with symptomatic STIs in 3 public and 3 non-government organisation operated clinics. Results: Out of 1339 index cases, partner referral was achieved by 37% in the counselling group and 27% in the non-counselling group. Index cases in the counselling group and non-counselling group were similar in terms of condom use rates, STI symptoms and duration of disease. A quarter of the index cases reported having more than one sex partner in last 3 months, and 39% reported having commercial sex partners. Only 8% of the index cases reported using condoms during their last sex act. Partner referral rates were higher among index clients with higher age, higher income, those who attended NGO clinics, those who had only one partner and among those who had no commercial partners, but counselling had significantly positive impact in all of these subgroups. In multivariate analysis, the probability of partner referral was 1.3 times higher among index cases in the counselling group (prevalence ratio 1.3; 95% CI 1.1 to 1.6) as compared to index cases in the non-counselling group. Conclusions: Patient-oriented single session counselling was found to have a modest but significant effect in increasing partner referral for STIs in Bangladesh, greater emphasis should be placed on examining further development and dissemination of partner referral counselling in STI care facilities.